Evidences for diabetes and insulin mimetic activity of medicinal plants: Present status and future prospects. Issue 12 (13th August 2017) - Manukumar, H. M.; Shiva Kumar, J.; Chandrasekhar, B.; Raghava, Sri; Umesha, S.
ABSTRACT: Diabetes mellitus (DM) is a considerable systemic metabolic disorder to exhibit various metabolic and cardiovascular disorders, mainly hyperglycemia. The global projected estimate of diabetes in 2030 will be about 439 million adults, out of which 300 million expected are of type-2 diabetes mellitus (T2DM). The present knowledge revealed responsible factors, occurrence and mechanism of these factors involved in the DM diseases. Hence, the aim of this review is to address and summarize the causes, plant resources, importance, present status and future programmes for diabetes control. The present review answers the contemporary present questions raised in the scientific field on DM. Two major problems are explained in detail about the autoimmune attack or dysfunction of β-cell and insulin resistance involved for Type 1 and Type 2 DM, respectively. Though there are various approaches to reduce the ill effects of diabetes and its secondary complications, many preferred herbal formulations due to lesser side effects and low cost. For this reason still it is getting increased attention in searching antidiabetic medicinal plants for hot research and to develop targeted medicine. Recurrence of islet autoimmunity lesson from pancreatic islet cell transplantation to cure T1D was outlined. With these highlights, the review summarizes the current knowledge on diabetes occurrence, factors (environmental and genetics), and types (I, II, gestation, and secondary DM), antidiabetic plants, sources for insulin mimetic plant principle compounds and their target mechanism with current and future trusted research areas for controlling of DM.